MEMAHAMI KARYA ILMIAH MELALUI PENERAPAN KETERAMPILAN MEMBACA SEKILAS DAN KRITIS - Isyatur Radhiyah (Cross-border, 2021)
This study aims to describe application skimming and critical reading skills in understanding scientific works. This is descriptive qualitative research, to find out and solve problems related to data in the form of a narrative from an observation. Reading is very important because reading is a process undertaken to obtain messages or information. In essence, reading is a process that is both physical and psychological, which we observe visually writing and thinking in processing information in the text. By skimming and critically reading scientific works, we can get benefits, one of which can add insight knowledge. Therefore, let's read, read and continue reading.